TO THE PROBLEM OF PSYCHOLOGICAL ADAPTATION OF THE STUDENTS WITH DISABILITIES TO STUDY AT THE HIGHER EDUCATIONAL ESTABLISHMENT - Гуляєва, Олена Володимирівна; Гуляєва, Юлія Олександрівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
Nowadays the model for adaption complex in students with disabilities for studying in higher educational establishments is being developed and implemented that supposes the following main components: 1) physical adaptation to the space of institution (spatial component); 2) inclusion in the educational process (educational component); 3) adaptation to the environment of course-mates and faculty staff (socio-psychological component).In comparison with spatial component, educational and socio-psychological components are not well-developed.Scientists define the following factors of successful professional adaptation of the students with disabilities: basic level of preparation for study at university; correspondence of skills and experience with the volume and level of knowledge of academic activity; aspiration to acquire the chosen profession and to work in the given field; interest to the subjects of the general and special cycle; acquisition of skills to work independently; availability of tutors’ institution; professional and pedagogical expertise of teaching staff; psychological monitoring of teaching process and etc.  Students with disabilities face the specific difficulties in the process of interaction with course-mates. These difficulties are connected with the course-mates not always being able to perceive and accept such people adequately. While showing sympathy, patience and understanding to these students, notionally healthy students are not eager to consider them as their friends and spend free time with them. On the other hand, the difficulties in interaction with course-mates and teachers for the students with disabilities resulted from their communicative skills – adequate self-expression in the process of communication, tendency to establish tight contacts, orientation to the compromise and cooperation.The process of adaptation of the students with disabilities to study at higher educational establishments is a complex and specific process. The specifics of the considered process is due to negative impact of student’s disability on it. Therefore, the process of adaptation to study at the university occur in two ways: adaptation to the outer conditions of the learning process and by way of displaying activity with the aim of overcoming own disability. Despite the described ways of students with disabilities adaptation to the learning process at higher educational establishments are closely connected, that is the second way that is considered to be the most successful one.